1113. Clinical and Virologic Outcomes with Early Adintrevimab (ADI) Monoclonal Antibody Therapy in Mild and Moderate COVID-19. (15th December 2022) - Mahoney, Kathryn; Narayan, Kristin; Betancourt, Natalia; Li, Yong; Gupta, Deepali; Hawn, Pamela; Schmidt, Pete; Popejoy, Myra
Abstract: Background: Peak SARS-CoV-2 viral replication occurs in the upper respiratory tract in presymptomatic and early symptomatic phases. Administration of a monoclonal antibody may be most beneficial in the early time period immediately after symptom onset. Here we describe the effect of early therapy on efficacy in patients receiving ADI. Methods: High risk patients with mild or moderate COVID-19 were enrolled in the ADI treatment study (STAMP), with primary endpoint of COVID-19 related hospitalization or all-cause death through Day 29 in patients with disease due to confirmed or suspected SARS-CoV-2 variants other than Omicron. Patients were randomized 1:1 to receive ADI or placebo administered by a single intramuscular (IM) injection. For this subgroup analysis, patients that had received therapy within 3 days of symptom onset were evaluated. Results: In the overall population, the study met the primary endpoint demonstrating 66% relative risk reduction of COVID-19 hospitalization or all cause death in 336 patients. Among 261 patients receiving therapy within 3 days of symptom onset (n=133 ADI, n=128 placebo), ADI was associated with a statistically significant reduction in the risk of COVID-19-related hospitalization or all-cause death through Day 29 compared with placebo (4 [3%] vs. 15 [11.7%], standardized risk difference -8%, 95% CI: -14.11, -1.86, p=0.0106), demonstrating a 72% standardized relative risk reduction in favor of ADI. When given as early therapy, ADI provided a greater reduction in viral load from baseline to Day 5 compared with placebo as assessed by saliva samples, with an adjusted least-squares mean difference of -0.97 log10 copies/mL (95% CI: -1.540, -0.391; p=0.0011). No study drug related SAEs, including deaths, and no hypersensitivity reactions were reported. Conclusion: Early therapy with a single dose of ADI 300 mg IM provided a 72% reduction in the risk of COVID-19 related hospitalization and all-cause death compared to placebo in high-risk ambulatory patients with mild to moderate COVID-19. Therapy within the first 3 days also led to a greater reduction in viral load compared to placebo and favorable outcomes in patients who are at high risk for progression of disease. Disclosures: Kathryn Mahoney, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Kristin Narayan, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Natalia Betancourt, MS, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Yong Li, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Deepali Gupta, B.Sc, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Pamela Hawn, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Pete Schmidt, MD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Myra Popejoy, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds.